ANALISIS KESALAHAN SISWA DALAM MEMECAHKAN SOAL MATEMATIKA MATERI ALJABAR BERDASARKAN NEWMAN ERROR ANALYSIS - Rohilah, Lailatur; Anugraini, Asri Putri; Kartika, Era Dewi (Universitas Insan Budi Utomo, 2024)
Algebra is basic material in mathematics lessons which has an important role and needs to be mastered by students. Therefore, students, especially MTs/SMP students, must understand algebra concepts well. This research aims to determine the types of errors made by students and the factors that cause students to make these errors. The research method used is qualitative with a descriptive type. Meanwhile, the research subjects were class VII students at MTs An-Nahdloh Candibinangun. This research took the form of 2 tests, namely an algebraic arithmetic operation test and story questions. The results of the research showed that the types of errors made by students in completing algebraic calculation operation questions were 61.42%, the factors causing errors were students' lack of understanding of the concept of variables and lack of focus on different calculation operations. Meanwhile, the story test questions showed that the types of errors made by students were conclusion errors, namely 28.57%, the factor causing errors was because students found it difficult to capture important information in the questions.